HIPCAR - Privacy and data protection : model policy guidelines & legislative texts (ITU Place des NationsCH, 2013)
Aims to ensure the protection of privacy and personal information to the satisfaction of the individual. Focuses on appropriate confidentiality practices within both the public and private sectors.
HIPCAR's objective is to assist CARIFORUM Countries in the Caribbean to harmonise their information and communication technology (ICT) policies, legislation and regulatory procedures.\n \n